Recommendations for dispensing magnesium products in pharmacy practice and primary health care - Merks, Piotr; Religioni, Urszula; Jakubowska, Marta; Parakkal, Sainul Abideen; Abdulsalim, Suhaj; Neumann-Podczaska, Agnieszka; Chełstowska, Beata; Unnikrishnan, Mazhuvanchery Kesavan; Szatko, Alicja; Glinicki, Piotr; Thorakkattil, Shabeer Ali; Doniec, Zbigniew; et al. (Family Medicine & Primary Care Review, 2024)
Magnesium is involved in many essential functions in the body, with a deficiency leading to possible cardiological, metabolic, neurological and rheumatological diseases, among others. The results of studies on the relationships between the occurrence of these diseases and magnesium deficiency helped identify the groups of patients who could benefit from this element. Considering the high frequency of patients using community pharmacy services, pharmacists present a group of medical professionals that can readily diagnose a potential magnesium deficiency in a relatively easy manner and can recommend supplementation in the diet or magnesium deficiency treatment with medicinal products when there are symptoms. For this reason, the objective of this article is to suggest procedures that can be used to identify patients particularly susceptible to magnesium deficiency. The second objective is to create Figures for the management of patients suffering from disorders that, in accordance with current knowledge, are associated with magnesium deficiency. In this context, guidelines were developed to help identify magnesium deficiency in patients with type 2 diabetes, insulin resistance, migraines, fibromyalgia, depression, anxiety states or hypertension. Appropriate supplementation with magnesium and magnesium deficiency treatment in the indicated target groups can largely minimize the symptoms of the diseases and increase patient wellbeing.